Treatment-Related Toxicities During Anti-GD2 Immunotherapy in High-Risk Neuroblastoma Patients - Blom, Thomas; Lurvink, Roosmarijn; Aleven, Leonie; Mensink, Maarten; Wolfs, Tom; Dierselhuis, Miranda; van Eijkelenburg, Natasha; Kraal, Kathelijne; van Noesel, Max; van Grotel, Martine; Tytgat, Godelieve (Frontiers in Oncology, 2021)
The introduction of immunotherapy using an anti-GD2 antibody (dinutuximab, ch14.18) has significantly improved survival rates for high-risk neuroblastoma patients. However, this improvement in survival is accompanied by a substantial immunotherapy-related toxicity burden. The primary objective of this study was to describe treatment-related toxicities during immunotherapy with dinutuximab, IL-2, GM-CSF, and isotretinoin. A retrospective, single center analysis of immunotherapy-related toxicities was performed in twenty-six consecutive high-risk neuroblastoma patients who received immunotherapy as maintenance therapy in the Princess Máxima Center (Utrecht, The Netherlands). Toxicities were recorded and graded according to the CTCAE. Particular attention was drawn to pain and fever management and toxicities leading to dose modifications of dinutuximab and IL-2. Twenty-three patients (88%) completed all six courses of immunotherapy. Disease progression, isotretinoin-associated liver toxicity, and catheter-related infection in combination with peripheral neuropathy were reasons for immunotherapy discontinuation. The most common grade ≥3 toxicities for courses 1–5, respectively, were pain, catheter-related infections, and fever. In total, 310 grade ≥3 toxicities were recorded in 124 courses. Thirty-three grade 4 toxicities in 19/26 patients and no grade 5 toxicities (death) were seen. Fifty-nine percent of grade ≥3 toxicities were recorded in the two courses with IL-2. Catheter-related bloodstream infections were identified in 81% of patients. Four of these episodes led to intensive care admission followed by full recovery (grade 4). Immunotherapy-related toxicities after induction and consolidation according to the Dutch Childhood Oncology Group (DCOG) NBL2009 treatment protocol are considerable but manageable. More toxicity is observed in the immunotherapy courses containing IL-2.